A Resected Case of Combined Hepatocellular and Cholangiocellular Carcinoma with Hemobilia from Intraductal Tumor Thrombus - Ikeguchi, Masahide; Katano, Kuniyuki; Saito, Hiroaki; Hirooka, Yasuaki; Endo, Kanenori; Osaki, Tomohiro (Nippon Shokaki Geka Gakkai zasshi, 2007)
A 73-year-old woman with hepatocellular carcinoma (HCC) reported the sudden onset of abdominal pain and Dynamic computed tomography (CT) showed a tumor in the liver (S4), a high-density mass in the common bile duct, and dilation of the peripheral bile duct. Gastrointestinal endoscopy showed bleeding from the papilla of Vater. Based on a diagnosis of HCC with hemobilia from the intraductal tumor thrombus, we conducted extended left hepatectomy and complete removal of the intraductal tumor thrombus. Histological findings showed combined hepatocellular and cholangiocellular carcinoma. Although recurrent lesions were detected, she remains alive and well 24 months after surgery. There has been one case of combined hepatocellular and cholangiocellular carcinoma with hemobilia from intraductal tumor thrombus reported in Japan to date. The prognosis of a patient suffering from HCC with hemobilia from intraductal tumor thrombus is dismal, but several cases reported indicate the possibility that surgical resection may improve prognosis. Adequate hepatic resection with complete removal of the intraductal tumor may thus improve the prognosis patients with combined hepatocellular and cholangiocellular carcinoma with hemobilia from intraductal tumor thrombus.